2005
DOI: 10.1152/ajpgi.00328.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-4 is required for intestinal response to epithelial injury and limiting bacterial translocation in a murine model of acute colitis

Abstract: Inflammatory bowel disease (IBD) arises from a dysregulated mucosal immune response to luminal bacteria. Toll-like receptor (TLR)4 recognizes LPS and transduces a proinflammatory signal through the adapter molecule myeloid differentiation marker 88 (MyD88). We hypothesized that TLR4 participates in the innate immune response to luminal bacteria and the development of colitis. TLR4-/- and MyD88-/- mice and littermate controls were given 2.5% dextran sodium sulfate (DSS) for 5 or 7 days followed by a 7-day recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
373
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 458 publications
(410 citation statements)
references
References 61 publications
24
373
4
2
Order By: Relevance
“…We and others have used an acute model of colitis to address the function of TLR4 in the setting of epithelial injury and inflammation. Administration of DSS to animals genetically deficient in TLR4 or MyD88 results in greater toxicity manifested by increased rectal bleeding, weight loss and mortality compared to wild-type littermates [14][15][16] . We have also found that animals deficient in TLR4 or MyD88 have decreased neutrophil recruitment to the intestine due to defective expression of chemokines and they experience bacterial translocation to mesenteric lymph nodes 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have used an acute model of colitis to address the function of TLR4 in the setting of epithelial injury and inflammation. Administration of DSS to animals genetically deficient in TLR4 or MyD88 results in greater toxicity manifested by increased rectal bleeding, weight loss and mortality compared to wild-type littermates [14][15][16] . We have also found that animals deficient in TLR4 or MyD88 have decreased neutrophil recruitment to the intestine due to defective expression of chemokines and they experience bacterial translocation to mesenteric lymph nodes 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, TLR4 signaling in response to pathogenic infection results in intestinal epithelial chemokine expression and the recruitment of inflammatory cells and intraepithelial dendritic cells 15-17 . We and others have explored the role of TLR4 in intestinal epithelial homeostasis and defense against pathogens. TLR4 knockout mice develop worse clinical symptoms of colitis following injury with dextran sodium sulfate (DSS) 18,19 . Underlying this phenotype, TLR4 knockout mice have decreased intestinal epithelial cell proliferation, decreased recruitment of inflammatory cells, and increased bacterial translocation to mesenteric lymph nodes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…An allele of murine TLR4, Lpsd, was first noted to decrease the severity of experimental colitis induced by dextran sulfate sodium (DSS), 6 and more recently, TLR4 À/À and MyD88 À/À mice have been shown to have more severe DSS-induced colitis than their wild-type littermates. [7][8][9] In addition, mutations in CARD15/NOD2 have been associated with susceptibility to human CD [10][11][12] and shown to affect nuclear factor-kB (NF-kB) activation, interleukin (IL)-1b processing, and resistance to intestinal Listeria monocytogenes infection in mice. 13,14 Within the TLR family of PRR, there are 10 different transmembrane receptors (TLR1-10) that are found either on the extracellular surface of cells (TLR1, 2 and 4) or within intracellular compartments such as endosomes (TLR3 and 7-9).…”
Section: Introductionmentioning
confidence: 99%